(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Tribal women serve as the backbone of the socio-economic and cultural fabric of indigenous communities in India. Their contributions to agriculture, forest-based livelihoods, domestic maintenance, and community well-being are unparalleled. Yet, despite their extensive involvement in subsistence activities, their voices remain less documented, and their socio-economic struggles often remain unaddressed. This study explores the multidimensional roles, challenges, and lived experiences of tribal women in Valagiri, Shenbaganur, Perumalmalai, Poomparai, and Mannavanur of the Kodaikanal region. Using an interview schedule and convenience sampling method, primary data were collected from 349 respondents. Percentage analysis was adopted to interpret the findings. Results show that tribal women face a disproportionate workload, combining wage labour, agricultural tasks, and complete responsibility for household and childcare duties. Limited access to education, healthcare, financial independence, and decision-making opportunities restricts their socio-economic mobility. However, their influence in sustaining households and community systems remains substantial. The study emphasizes the need for policy interventions that strengthen their livelihood skills, improve health and education outcomes, and promote equitable participation in community development. Empowering tribal women is crucial not only for gender equality but also for the sustainable development of tribal communities.